2019
DOI: 10.32550/teknodik.v17i4.576
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Tik Dalam Meningkatkan Kompetensi Guru Paud Melalui Knowledge Management System Implementation of Ict in Improving Early Childhoud Education (Ece) Teacher Competence Through Knowledge Management System

Abstract: Abstrak: Tujuan penelitian ini adalah untuk mengetahui penguasaan kompetensi guru PAUD, khususnya kompetensi pedagogik dan kompetensi profesional. Penelitian ini merupakan penelitian pengembangan dalam mengimplementasikan website sistem pembelajaran melalui sharing Knowledge Management System (KMS). Pada penelitian pendahuluan ini diketahui bahwa secara umum penguasaan kompetensi pedagogik dan kompetensi profesional yang dipersyaratkan sebagai guru PAUD masih rendah. Oleh karena itu salah satu pemecahannya ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The availability of digital literacy infrastructure in schools is based on findings in the field in this study, including computers, laptops, school cellphones, Internet access, projectors and cameras. Based on the research results of Sugiarti et al (2013), it is found that early childhood teachers in Indonesia are already used to operating mobile phones and the Internet (chatting, social networking and email). However, the use of this technology is still only for entertainment and communication purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of digital literacy infrastructure in schools is based on findings in the field in this study, including computers, laptops, school cellphones, Internet access, projectors and cameras. Based on the research results of Sugiarti et al (2013), it is found that early childhood teachers in Indonesia are already used to operating mobile phones and the Internet (chatting, social networking and email). However, the use of this technology is still only for entertainment and communication purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Fan and Tan (2019) identified the application of technology to the organization of educational activities for preschool children as one of the most essential professional competencies required of preschool teachers. Based on the findings of (Sugiarti et al, 2013), the implementation of technology in the capacity building of preschool educators through the Knowledge Management System seeks to investigate the challenges the preschool teachers encounter in capacity development, particularly educational and professional capacity. Information technology creates standards for organizing organizations to provide the necessary conditions for the professional growth of teachers, enhancing their qualifications and assisting by not only understanding the causes of career difficulties but also determining the nature of each career goal (Shnejder et al, 2020).…”
Section: Preschool Teacher's Professional Competencementioning
confidence: 99%
“…Lebih jauh lagi, hasil penelitian dari Susanti (2020) menunjukkan bahwa teknologi belum banyak dimanfaatkan secara maksimal oleh guru, dimana banyak pendidik belum dapat memanfaatkan teknologi sebagai media pembelajaran. Sejalan dengan hal tersebut, penelitian yang dilakukan oleh Sugiarti et al, (2019) menunjukkan bahwa rendahnya kompetensi pedagogik dan kompetensi profesional yang dikuasai oleh guru PAUD berkorelasi dengan tingkat pendidikan yang sebagian besar masih lulusan SLTA, oleh karena itu perlu diupayakan peningkatan kompetensi di luar pendidikan formal, yaitu dengan memanfaatkan Teknologi Informasi dan Komunikasi (TIK), dimana pemanfaatan TIK yang semula hanya untuk komunikasi dan hiburan saja di ubah menjadi pemanfaatan TIK untuk mendukung peningkatan kompetensinya Melalui pembudayaaan memanfaatkan web sebagai sumber belajar dengan di akses melalui berbagai produk teknologi informasi dan komunikasi untuk keperluan pendidikan.…”
Section: Pendahuluanunclassified